Lactobacillus murinus Improved the Bioavailability of Orally Administered Glycyrrhizic Acid in Rats - Yuan, Tianjie; Wang, Jin; Chen, Letian; Shan, Jinjun; Di, Liuqing (Frontiers in Microbiology, 2020)
The intestinal microbiota has been extensively studied in the context of host health benefit, it has recently become clear that the gut microbiota influences drug pharmacokinetics and correspondingly efficacy. The intestinal microbiota dysbiosis is closely related with the liver cirrhosis, especially the depletion of Lactobacillus. Therefore, the bioavailability of orally administration of Glycyrrhizic acid was speculated to be influenced under the pathological status. In present study, L.murinus was isolated and screened for the GL bioconversion capacity in vitro. Compared with L.rhamnosus and L.acidophilus, L.murinus was chose for further investigation due to the highest biotransformation rate. Our results showed that L.muriuns could significantly improve the translocation of GL on Caco-2 cell models. Meanwhile, L.murinus was observed to have the ability to bind with the surface of Caco-2 cell and prominently downregulate the transporter gene expression level of MDR1 and MRP-2, which involved in the efflux of the drugs. Furthermore, the L.murinus was selected to orally administrated into the rats on healthy and liver cirrhosis group respectively by a daily gavage protocol. Our data highlighted that supplements of L.murinus significantly improve the orally administrated GL bioavailability in rats, especially under the pathological condition, which may provide the novel strategy for improving the clinical therapeutic effect of liver protective drugs.